Itinerary of home. - Wilkes, Kerry J. (Curtin University, 2000)
Embodied in my art practice is the exploration of the relationship between my subjective self as consumer and the material culture of home. As an artist this praxis suggests alternative ways of reconstructing domestic subjectivity (self-portrait) through the formal processes of drawing and cataloguing insignificant collections acquired through 'lived experience'. This analysis utilises Michel de Certeau's concept of bricolage, a 'tactic' of fragmentation that 'makes do with what is at hand' to corrupt the 'proper' space and time of a contemporary productionist society. In the course of developing an art practice, I seek to re-value marginal space and reappropriate time from a modern culture designed for efficiency.Through the introduction of key elements in process drawing, I have adopted a method to subvert modernist representations of the domestic. As Certeau writes 'mak[ing] use of techniques of re-employment in which we can recognise the procedures of everyday practice' is a political deployment, an individual 'tactic' orchestrated against social 'strategy'. A fragmentary tactical operation allows me fleeting moments of visibility to record 'lived experience' through an installation based art practice.